Status of Exploited Fishery Resources of Azhikode Estuary, Kerala, India - Harikrishnan, M; Vipin, P M; Kurup, B Madhusoodana (Fishery Technology, 2025)
The exploited fishery resources in Azhikode estuary have been quantified as 360.02 t and 424.80 t during 2005-06 and 2006-2007, respectively, with a mean annual catch of 392.2 t. Finfishes accounted for 47% of total landings, followed by molluscs (32%) and crustaceans (21%). Thirty finfish species belonging to 18 families, 6 species of penaeid shrimps, 2 species of palaemonid prawns, 2 species of crabs and 4 species of bivalves contributed to the exploited fishery. Catfishes, mullets, Gerres spp., pearlspots and snappers were the major groups of finfish species while Metapenaeus dobsoni and Fenneropenaeus indicus formed the bulk of shrimp landings. Scylla serrata represented the bulk of crab landings of 8-12 t. The catch of Villorita cyprinoides from the estuary has been estimated to be between 120 and 135 t. Highest landings were observed during pre-monsoon period in both years (55.32-63.78%), followed by postmonsoon (27.63-25.76%) and the lowest was during monsoon (17.06-10.46%). More than 50% of fish catch in the estuary was contributed by fixed engines such as Chinese dip nets and stake nets. Finfishes accounted for the highest production per ha during both the years (0.68-0.83 t ha-1yr-1) followed by clams (0.45-0.56 t ha-1yr-1) and shrimps and prawns (0.27- 0.34 t ha-1yr-1). Fish production in the estuary showed a steady increase from monsoon to pre monsoon and majority of species supporting lucrative fishery in the estuary showed maximum occurrence during high saline months.